Lactic Acid Bacteria as Probiotics Improve Bioactive Compounds in Radix Angelica gigas (Danggui) via Solid-State Fermentation - Jeong Heo; Youn-Kyung Ham; Ah Yeong Choi; Hyouk Yoon; Ha Gyun Sung (Fermentation)
Solid-state fermentation (SSF) is increasingly applied to enhance the functional properties of traditional herbal medicines. In this study, we investigated the effect of lactic acid bacteria (LAB) and other probiotic strains on the bioactive profile of Radix Angelica gigas (Danggui) during SSF. SSF was carried out by incubating a mixture of the herbal powder and distilled water (1:1, pH 7.0) with LAB strains (Lactobacillus rhamnosus, L. acidophilus, L. buchneri, L. reuteri, L. plantarum) and additional microbes (Bacillus subtilis, Saccharomyces cerevisiae) under controlled conditions. The 2,2-Diphenyl-1-picrylhydrazyl (DPPH) and 2,2′-Azino-bis(3-ethylbenzothiazoline-6-sulfonic acid) (ABTS) radical scavenging activities and total phenolic and flavonoid contents were measured. L. buchneri exhibited the highest growth, with significant proliferation observed on days 4 and 6, especially at 30 °C (p < 0.05). The DPPH and ABTS radical scavenging activities and total phenol and total flavonoid contents were increased by up to 230% (35 °C), 111% (30 °C), 137% (30 °C and 35 °C), and 133% (35 °C), respectively, in fermented herbs compared with those in non-fermented herbs. Antioxidant levels (DPPH, phenol, and flavonoid) exhibited a significant positive correlation with bacterial growth and a significant negative correlation with pH in SSF, but ABTS did not exhibit any statistically significant correlation with bacterial growth or pH. Moreover, multi-strain fermentations involving L. acidophilus and L. plantarum significantly increased the antioxidant activities compared to single-strain fermentations (p < 0.05). These findings suggest that SSF using probiotic LAB can significantly improve the bioactive composition of Radix Angelica gigas, providing a scientific method for modernizing traditional herbal medicine with potential uses in human and animal health.